India and the Islamic heartlands : an eighteenth-century world of circulation and exchange - Sood, Gagan, D. S. (Cambridge Univeersity Press, 2016)
"Based on the chance survival of a remarkable cache of documents, India and the Islamic Heartlands recaptures a vanished and forgotten world from the eighteenth century spanning much of today's Middle East and South Asia. Gagan Sood focuses on ordinary people--traders, pilgrims, bankers, clerics, brokers, scribes, among others--who were engaged in activities marked by large distances and long silences. By elucidating their everyday lives in a range of settings, from the family household to the polity at large, Sood pieces together the connective tissue of a world that lay beyond the sovereign purview. Recapturing this obscured and neglected world helps us better understand the region during a pivotal moment in its history, and offers new answers to old questions concerning early modern Eurasia and its transition to colonialism"--